DEVELOMENT OF THE HEALTH SCHOOL A CASE STUDY OF NON SANGSRI IN THE MUKDAHAN PRIMARY EDUCATIONL SERVICE AREA OFFICE - Puangyod, Paitoon (Journal of Buddhist Anthropology, 2020)
This research article aims to 1) study the state of development of healthy schools, 2) study the guidelines for developing healthy schools in a case study. Ban Nonsangsri School Mukdahan Primary Educational Service Area Office It is a mixed research method. Population and Sample/Key Informants They were administrators, teachers, school committees, students, and parents, totaling 50 people. Selected samples/key informants by purposive method. The research tools were questionnaires, 5-point estimation scales, and structured interviews. Statistics used were percentage, mean, and deviation. standard ben The results showed that 1) State of health school development The overall development was at a high level ( = 4.46) and the development of health schools was at a high level. The researcher ranked them in descending order of school happiness ( = 4.47), student happiness ( = 4.46), community happiness ( = 4.46), environment happiness ( = 4.45), and family happiness. ( = 4.42) and2) Guidelines for developing healthy schools, health schools, case studies Ban Nonsangsri School Mukdahan Primary Educational Service Area Office characteristics of good learners Being healthy is a person who has good physical health. Keep up with digital technology and have good mental health. have a strong physical health dare to think Conscience of love for homeland, drug-free The characteristics of a good school should have a flexible and equal management system. Characteristics of a good environment environment with natural trees good relationships are created and role models for learners, public mind, family participation in learning management, good community characteristics should develop relationships with community participation network community free from all kinds of drugs